2022
DOI: 10.33380/2305-2066-2022-11-1-140-147
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics Study of the Long-acting Antiarrhythmic Drug of Lappaconitine Hydrobromide (Allaforte®, JSC "Pharmcenter VILAR", Russia)

Abstract: Introduction. Allaforte® (JSC "Pharmcenter VILAR", Russia) is an antiarrhythmic long-acting drug. The dosage form of the drug Allaforte® provides a decrease in the frequency of taking the drug and also reduces the risk of side effects. It is relevant when taking antiarrhythmic drugs of the IC class. However, the pharmacokinetics of this drug has not been studied on humans. Therefore, it is important to fully study the pharmacokinetics to ensure the maximum efficacy and safety of arrhythmia therapy.Aim. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Allapinin (lappaconitine) is one such drug, which has antiarrhythmic activity through the inhibition of tetrodotoxin-sensitive, voltage-dependent sodium channels [ 8 , 9 ]. This substance is used in clinical practice in China and Russia for the treatment of supraventricular and ventricular arrhythmias [ 10 , 11 ]. However, this substance has a number of disadvantages: the high toxicity of the drug [ 12 , 13 ]; difficulty in the calculation of the therapeutic dose due to its cumulative accumulation in organs and tissues and non-linear pharmacokinetics [ 14 ]; having a short period for maintaining the therapeutic concentration of the drug in the blood [ 14 ]; and the occurrence of other side effects such as chills, shock, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allapinin (lappaconitine) is one such drug, which has antiarrhythmic activity through the inhibition of tetrodotoxin-sensitive, voltage-dependent sodium channels [ 8 , 9 ]. This substance is used in clinical practice in China and Russia for the treatment of supraventricular and ventricular arrhythmias [ 10 , 11 ]. However, this substance has a number of disadvantages: the high toxicity of the drug [ 12 , 13 ]; difficulty in the calculation of the therapeutic dose due to its cumulative accumulation in organs and tissues and non-linear pharmacokinetics [ 14 ]; having a short period for maintaining the therapeutic concentration of the drug in the blood [ 14 ]; and the occurrence of other side effects such as chills, shock, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Wenxiu et al demonstrated the possibility of immobilizing allapinin in the ionic biopolymer iota–carrageenan with a loading efficiency of 26.18% [ 15 ]. However, the total time of drug release from the iota–carrageenan complex in an aqueous medium at 37 °C and pH 7.4 was not more than 6 h, which may be insufficient because, according to the pharmacokinetic profile of the standard drug, its maximum concentration in the blood is maintained for 12 h after oral administration [ 11 ]. At the same time, lowering the pH of the incubation solution to 6.6 results in the complete release of the drug within 3 h of incubation, which may adversely affect the therapeutic effect of the drug in crossing the gastric acid barrier.…”
Section: Introductionmentioning
confidence: 99%
“… Newman and Cragg (2020) reported that from 1981 to 2019 there was 1881 new remedies, which were approved for medical application, and the 22.9% of them are of natural origin. Phytotherapy plays an important role in the treatment of cardiovascular ( Kirichenko et al, 2020 ; Archakova et al, 2022 ; Karahan et al, 2022 ), immune ( Babich et al, 2020 ; Ligacheva et al, 2022 ; Abdugafurova et al, 2024 ), cancer ( Medvedev et al, 2020 ; Kitaeva et al, 2022 ; Jia-Xing et al, 2023 ), and infectious diseases ( Gorlenko et al, 2020 ; Luzhanin et al, 2022 ; Zrig, 2022 ). According to the WHO, herbal medications are the main choice in many regions of the world ( Aware et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%